Innocence: Semiotic Configuration of an Ethical Proposal in the Lyrical Discourse of Rómulo Bustos Aguirre - Chico Quintana, Rafael Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper synthetically presents the results of a research project conducted between 2011 and 2013, communicating its results as well as relevant aspects of the interpretation and analysis process. Twelve poems by the Colombian author Romulo Bustos Aguirre were analyzed in order to disclose the ways in which their semiotic configuration expresses an ethical proposal. To demostrate the analysis process in depth, we will focus on a representative poem, chosen from the corpus which replicates aspects of the semiotic configuration unifying our corpus. The theoretical and methodological framework that support the interpretation and analysis process involve the Semiotic Discourse Analysis theory developed by the School of Paris, as well as the semic analysis and lexical-semantic models of the Interpretive Semantics theory developed by François Rastier